Pengaruh Inflasi, BI Rate, Jumlah Uang Beredar, dan Nilai Tukar Terhadap Nilai Outstanding Sukuk Korporasi (Periode 2018-2022) - Nabila Imam; Karfin (Prodi Ekonomi Syariah IAIN Sorong, 2024)
Islamic law prohibits Muslims from raising capital through debt and participating in the debt market. To address this, a sharia-based product like sukuk was developed. A study analyzed the impact of inflation, BI rate, money in circulation, and exchange rate on the outstanding values of corporate affiliates in Indonesia from January 2018 to December 2022. The results showed that inflation and BI rates significantly negatively influenced the outstanding value of corporate affiliates, while the amount of money in circulation and exchange rates had a significant positive influence. The exchange rate had no significant influence. The study highlights the importance of economic stability and monetary policy in supporting the development of corporate affiliate markets in Indonesia.